How do athletes perform well under pressure? A meta-study - Hufton, J. R.; Vella, S. A.; Goddard, S. G.; Schweickle, M. J. (International Review of Sport and Exercise Psychology, 2026)
Many studies have explored athlete performance under pressure, with recent emphases on choking prevention and definitions of clutch performance. Whilst these two areas may benefit sport performance research, it may also be important to explore the prominent factors in facilitating athlete performance under pressure to promote the development of interventions targeting clutch performance in the future. In the present review, we synthesised qualitative research on athlete performance under pressure to highlight the psychological factors and strategies useful in facilitating performance under pressure in sport. Given the difficulties in reviewing and conducting quantitative research on these concepts (e.g. there currently is no validated measure of pressure), we chose to review qualitative research. Database searchers were conducted in September 2022, August 2023, and August 2024. This resulted in the identification and meta-synthesis of 29 articles reporting qualitative findings. Athletes, coaches, and sporting practitioners considered self-efficacy, demand appraisal, mental toughness, and task-focused resource allocation as important in facilitating athlete performance under pressure. Pre-performance routines, imagery techniques, self-talk, goal setting, cognitive restructuring, and simulated pressure training were also reported as useful strategies to facilitate athlete performance under pressure.